Materials selection for hip prosthesis by the method of weighted properties - Hamidi, Ehsan (Penerbit UTM Press, 2015)
Process of materials selection for an artificial part, which is planted in vivo, has been always a vital procedure. Production and construction requirements for implants would involve a wide variety of considerations from mechanical specifications to medical limitations. From mechanical point of view, it is desired the implant exhibits mechanical properties of the missing bone as close as possible to reduce the risk of failure and provide a high level of comfort to the patient. The most bolded medical trait that prostheses must possess is the quality of biocompatible being; meaning that, they have to be accepted by the body’s living organisms. In this paper, five common biocompatible materials as candidates for hip prostheses production namely, 316L St Steel (cold worked, ASTM F138), Co–28Cr–6Mo (cast, ASTM F75), Ti–6Al–4V (hot forged, ASTM F620), Zirconia (ceramic, 3Y-TZP) and Alumina (ceramic, ZTA) are selected and evaluated by the method of weighted properties, in order to narrow down the search to find the candidate which best fit the real bone’s mechanical traits. For the analysis, six attributes were considered and weighted against each other namely, elastic modulus, yield strength, tensile strength, fatigue strength, corrosion rate and density. From the results, alumina and stainless steel show highest performance indexes but as it is discussed, due to the importance of biocompatibility required in practical, materials ranked on position 4th and 5th which are respectively of cobalt and titanium alloys–although are less mechanically similar to the real bone, are the most desirable choices in the industry. It will be concluded that in the process of materials selection for implants